The CAMH Neuroinformatics Platform: A Hospital-Focused Brain-CODE Implementation - Rotenberg, David J.; Chang, Qing; Potapova, Natalia; Wang, Andy; Hon, Marcia; Sanches, Marcos; Bogetic, Nikola; Frias, Nathan; Liu, Tommy; Behan, Brendan; El-Badrawi, Rachad; Strother, Stephen C.; et al. (Frontiers in Neuroinformatics, 2018)
Understanding the human brain in both healthy function and in the context of psychiatric illness presents a formidable technical and analytic challenge for medical researchers. Multi-modal data, including medical imaging, molecular and clinical measures provide lenses through which the brain’s structure, function, expression and behavioral presentation can be studied. While directed integration of complementary information promises to accelerate discovery and identify cross-modal biomarkers for stratification, diagnosis and treatment, such approaches, require stringent data standardization and are often computationally demanding, compounded by increased data volumes, statistical power and sample size requirements. To realize the potential of multi-modal data integration toward the study of mental illness, the Center for Addiction and Mental Health (CAMH) constructed a centralized data capture, visualization and analytics environment – the CAMH Neuroinformatics Platform – based on the Ontario Brain Institute (OBI) Brain-CODE platform, enabling the curation of a standardized, consolidated psychiatric hospital-wide research dataset, directly coupled to high performance computing resources.